PELATIHAN CRAFT KAIN PERCA BAGI PEMBERDAYAAN DAN KESEJAHTERAAN KELUARGA RT.08 RW.05 DI KELURAHAN BANDUNG REJOSARI KOTA MALANG - Tri Yulistyawati Evelina; Rena Feri Wijayanti; Lina Budiarti; Erlangga Andi Sukma; Rizky Kurniawan Murtiyanto (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2017)
Family empowerment is all the guidance and coaching efforts for the family to live healthy prosperous, advanced and independent. Members PKK RT.08 RW.05 in Rejosari urban village of Malang Malang some of the mother-mother as a housewife.One proposed to the mother of PKK is a Craft Cloth Training. The reason for the selection of this training is that the training is not too difficult, it does not require special training so that for mothers who have other activities such as taking care of the family, shop business and so fits very well.The purpose of PKM activities are as follows: (1) To provide knowledge and skills for PKK mothers in handicraft processing using patchwork material; (2) To empower and prosper the family by creating business opportunities to supplement family income. While the expected benefits are: (1) As input to develop the program of empowerment and family welfare; (2) As inputs to find potential for PKK mothers in entrepreneurship. Implementation of their service activities as follows: (1) Pre Training; (2) Training Design; (3) Implementation of work skills training